The role of satisfaction with care among factors affecting health-related quality of life in people with cancer: a cross-sectional study - Sancassiani, Federica; Kalcev, Goce; Agus, Mirian; Mulas, Olga; Massa, Elena; Primavera, Diego; Origa, Giulia; Monni, Mariarita; Vacca, Veronica; Pibiri, Francesca; Nardi, Antonio Egidio; Madeddu, Clelia; et al. (Frontiers in Oncology, 2026)
BackgroundDespite advances in therapies that have increased the duration of post-diagnosis survival, living with long-term adverse effects of cancer and its treatment is common. This study aims to evaluate satisfaction with care (SC) as a dimension affecting Health-Related Quality of Life (HRQoL) among people with cancer, considering other sociodemographic and clinical variables supposedly impacting HRQoL.MethodsThis cross-sectional study used an ad hoc form to collect sociodemographic and clinical variables. The SF-12 and TPQ were used to evaluate HRQoL and SC, respectively. The relation between SC, socio-demographic, clinical variables (predictors), and HRQoL (criterion) was assessed using hierarchical linear regression, controlling for age, cancer stage, and time of care.Results263 patients (49.8% males; age 61.2 ± 13.8 years) from two cancer units. Positive correlations (p<0.05) between SC and HRQoL. Females have a poorer HRQoL than males (ß= .416, CI 95% [.162;.671], p=0.001), as well as patients from the hospital ward compared to those in the day hospital service (ß= -.459, CI 95% [-.782 -.137], p=0.005). Greater SC referred to the service features predict better HRQoL (ß= .338, CI 95% [.154;.523], p<0.001).ConclusionsGiven the cross-sectional design, causal inferences cannot be drawn; however, identifying satisfaction with care and other factors associated with HRQoL among people with cancer may help inform prevention and rehabilitation programs.